2018
DOI: 10.1182/blood-2018-99-119731
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection, but Not Hepatic Iron Overload Is the Dominant Risk Factor for the Manifestation of Hepatocellular Carcinoma Among Greek Thalassemic Patients

Abstract: Background: Effective iron chelation and other supportive treatment have a substantial impact on survival prolongation of thalassemic patients, who may reach late adulthood, and therefore, may manifest various neoplastic disorders. However, no systemic analysis of the prevalence of neoplastic disorders in this patient population has been performed. Aims: We systematically analyzed all cases of malignant neoplastic disorders, occurred in a large cohort of Greek thalassemic patients and investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Similar results were also reported in 63 Greek thalassemia patients with HCC (median age: 45 years). 11 Comparing our data with the results of a previous publication, 22 it emerges that our subgroup of NTDT patients with HCC were older (56.8 vs.47 years). However, our series consisted of 6 NTDT patients vs.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Similar results were also reported in 63 Greek thalassemia patients with HCC (median age: 45 years). 11 Comparing our data with the results of a previous publication, 22 it emerges that our subgroup of NTDT patients with HCC were older (56.8 vs.47 years). However, our series consisted of 6 NTDT patients vs.…”
supporting
confidence: 72%
“…However, several aspects remain to be explored further. HCC is more frequently diagnosed (at present) in men with TDT in their fourth -fifth decade and older in NTDT 11,22 with long-standing, untreated chronic hepatitis C (76%), irrespective of the content of hepatic iron load, estimated with MRI T2*. 11 One possible explanation is that patients with NTDT may have a milder process of iron overloading at late age and a lower incidence of chronic viral liver infections, mainly HCV.…”
Section: Pathophysiology Past and Recent Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the 2019 AIOM report, 33.000 patients had HCC diagnosis in Italy between 2013 and 2018 [12]. Among beta-thalassemia patients, HCC prevalence ranged from 2.3% in Greece to 1% in Italy [1,13]. Another study reported that HCC prevalence in male patients with beta-thalassemia is 6 times higher than in non beta-thalassemia subjects [14].…”
Section: Main Bodymentioning
confidence: 99%
“…HCC incidence, standardized by age in non beta-thalassemia patients can be estimated at 10.9/100.000 P/Y for male and 3.1/100.000 P/Y for female [ 13 ]. Incidence of 1.02/100.000 P/Y was estimated in the Italian Thalassemia Registry including 5855 patients [ 1 ].…”
Section: Main Bodymentioning
confidence: 99%